2015
DOI: 10.1177/2165079915592281
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Workload and Working Conditions on Operating Room Nurses and Technicians

Abstract: This study was conducted between August 15 and September 20, 2013, to determine the effects of workload and working conditions on operating room (OR) nurses and technicians. The study sample included 74 OR nurses and technicians working in a private university's six hospitals. The Individual Workload Perception Scale and a questionnaire that collected data on risk and environmental factors were used. The mean age of study participants was 29.3 ± 6.7 years, and 62.2% of the participants were female. More than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 27 publications
1
30
1
3
Order By: Relevance
“…This might be due to underreporting of injuries. This is not compatible with previous studies, which stated that nurses working in ORs and emergency and intensive care units were found to be at the highest risk for needle stick injuries (Chiou et al,2013,and Ugurlu et al, 2015.…”
Section: Discussioncontrasting
confidence: 96%
“…This might be due to underreporting of injuries. This is not compatible with previous studies, which stated that nurses working in ORs and emergency and intensive care units were found to be at the highest risk for needle stick injuries (Chiou et al,2013,and Ugurlu et al, 2015.…”
Section: Discussioncontrasting
confidence: 96%
“…In the present study, shift work scored as the third priority (weight: 0.251). Operating room and ICU nurses had a heavier workload compared to clinical nurses due to their shift work, which could lead to physiological, physiological, and social complications [25]. According to the findings of Portoghese et al (2014), workload causes exhaustion and low job control, which in turn lead to the low efficiency of the system [26].…”
Section: Resultsmentioning
confidence: 99%
“…The findings demonstrated that work-related burnout was the main extrinsic job satisfaction factor [16]. Other identified extrinsic factors include working conditions [43] and work engagement. A nurse's work satisfaction job was further linked with supervisor support [22] mobbing [28] and bullying [37].…”
Section: Discussionmentioning
confidence: 99%